Reliability Based Multireservoir System Operation for Mae Klong River Basin - Areeya Rittima; Varawoot Vudhivanich (Agriculture and Natural Resources, 2006)
Because of the uncertainty of hydrologic process and the increasing trend of water demand, the reliability-risk concept was adopted for evaluating a long term multireservoir system operation characteristics. The reliability based multireservoir operation model of Mae Klong River Basin was developed in term of limit state function by using the daily hydro-meteorological data from 1985 to 2004. The reliability concept was applied to classify the failure domain in terms of load and resistance. The failure domain was classified into 3 modes namely flood mode, shortage mode, and energy mode. The objective of this study was to evaluate the reliability indices of the existing and future system states and also to forecast the maximum possible firm yield of Mae Klong multireservoir system at the various reliability levels. The result showed that the existing operation at 6,975 mcm/yr of average water demand gave the good performance with the reliability of 98.60%, 99.80-100%, and 73.60% for mode 1, 2, and 3 respectively. If there was 25% increase of the average water demand, the reliability of shortage mode would decrease to 95.60% and the reliability of energy mode would decrease to 51%. However, it did not influence to the reliability of flood mode. The result of possible firm yield forecasting considered from shortage mode indicated that at the reliability of 80%, 85%, 90%, and 95%, the maximum possible firm yields were 10,979, 10,672, 10,114, and 9,451 mcm/yr respectively. In other words, if the higher shortage risk was allowed, the higher firm yield could be utilized.